Предмет: Алгебра,
автор: Аноним
КТО-НИБУДЬ Помогите пожалуйста упростить выражение:
1)(2√a+3√b)^2+(2√a+3√b)(2√a-3√b)=
2)(√m-√n)^2-(√m-√t)^2-(√n-√t)^2=
Ответы
Автор ответа:
0
1) = 4a+12√ab+9b+4a-9b = 8a+12√ab
2) = m-2√mn+n-m+2√mt-t-n+2√nt-t = -2√mn+2√mt-2t+√nt
2) = m-2√mn+n-m+2√mt-t-n+2√nt-t = -2√mn+2√mt-2t+√nt
Автор ответа:
0
СПАСИБО БОЛЬШОЕ
Похожие вопросы
Предмет: Математика,
автор: nurgule7707
Предмет: Информатика,
автор: kuznetsovd126
Предмет: Русский язык,
автор: russergeev0g
Предмет: Математика,
автор: katig791
Предмет: Физика,
автор: 1telepyzik